Utilization of Agricultural Waste for Cultivation of Paddy Straw Mushrooms (Volvariella volvacea (Bull.) Singer 1951) - Zikriyani, H.; Saskiawan, I.; Mangunwardoyo, W. (International Journal of Agricultural Technology, 2018)
Volvariella volvacea (Bull.) Singer 1951 or paddy straw mushroom is one of the edible mushroom that cultivated in the tropical and subtropical area. The mushroom usually is grown on the lignocellulosic agricultural waste as a substrate. The utilization of three kinds of agricultural waste as growth media: paddy straws, cotton wastes and banana leaves were used. The composted process was done in 7 days with the addition of 2% (w/w) of CaCO3, 20% (w/w) of rice bran and 0.5% (w/w) of urea fertilizer. The media were laid on the shelf in the 3.0 x 4.0 x 3.0 meter of mushroom house and pasteurized at 60--70°C for 4--6 hours. The spawn was inoculated when the temperature was colled down to be 35oC. The results showed mycelia have fully grown to cover the surface of media at 5 days (cotton wastes and paddy straws) and 6 days (banana leaves) after inoculation. The first fruiting body appeared at the egg stage of 7 days (paddy straws and cotton wastes) and 8 days (banana leaves). Proximate composition analysis showed that protein content was 37.38%, 27.95%, and 20.84% of paddy straws, cotton wastes and banana leaves repectively. Meanwhile, the carbohydrate content of 5.11%, 4.26% and 3.74% was obtained of banana leaves, cotton Wates, and paddy straws. The highest biological efficiency was shown from production using cotton Wates of 17.69%; banana leaves of 8.56%; and paddy straw of 7.93%. Statistical analysis showed no signifficant different on cultivation using cotton wastes, paddy straws and banana leaves (p<0,05).